Kemampuan Mikrob Endofit dan Rizosfer Tanaman Karet dalam Mengendalikan Rigidoporus lignosus - Siti Hardiyanti; Bonny Poernomo Wahyu Soekarno; Titiek Siti Yuliani (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Rigidoporus lignosus is the most important pathogen of rubber tree which causes white root rot disease. The use of antagonistic microbe is recommended to control this pathogen. This research was conducted to isolate endophytic and rhizospheric microbes, and to study their ability to inhibit growth of R. lignosus. Research consisted of isolation of endophytic and rhizospheric microbes, pathogenicity test, in vitro and in vivo assays, growth promotion assays, and identification. There were 99 isolates of bacteria and 18 isolates of fungi isolated from the root and rhizosphere of rubber trees. In vitro and in vivo assay showed that 2 bacterial isolates, i.e. endophytic bacteria ME8, and rhizospheric bacteria MR3; and 3 fungal isolates, i.e. endophytic fungi CB8, CB6, and CL3 were able to inhibit the growth of R. lignosus. Endophytic bacteria ME8 showed the ability of solibilizing phosphate and fixing nitrogen. Rhizospheric bacteria MR3 showed the ability of solubilizing phosphate. The isolates CB6 and CL3 were very similar with Chaetomium sp. and Penicillium sp., respectively based on morphological characters; while CB8 was identified as mycelial sterile. Based on 16S rRNA sequences, endophytic bacterium ME8 and rhizospheric bacteria ME3 were identified as Bacillus siamensis B268 and B. amylolyquefaciens BCRh10, respectively. Endophytic and rhizospheric microbes isolated from rubber trees has the potency as biocontrol agents of R. lignosus.